2021
DOI: 10.1109/tns.2021.3086686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Mitigating Neutrons Effects on COTS EdgeAI Accelerators

Abstract: EdgeAI is an emerging AI accelerator technology which is capable of delivering improved AI performance at both a lower cost and a lower power level. With the aim of implementation in large quantities and in safety-critical environments, it is imperative to understand how Single Event Effects (SEE) affect the reliability of this new family of devices, and to propose efficient hardening solutions. Through neutron beam experiments and faultinjection analysis of a COTS EdgeAI device, we are able to identify the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…At ChipIR, the lowest SDC cross section is measured for ResNet, a similar neural network as the one tested for the NeuroShield in [1]. Considering a 13n/cm 2 /h flux for atmospheric neutrons at sea level, the ∼ 19 × 10 9 cm 2 cross section of the ResNet neural network translates in about 270 FIT, very similar to the 10 2 FIT measured for the NeuroShield.…”
Section: B Neural Networksupporting
confidence: 54%
See 3 more Smart Citations
“…At ChipIR, the lowest SDC cross section is measured for ResNet, a similar neural network as the one tested for the NeuroShield in [1]. Considering a 13n/cm 2 /h flux for atmospheric neutrons at sea level, the ∼ 19 × 10 9 cm 2 cross section of the ResNet neural network translates in about 270 FIT, very similar to the 10 2 FIT measured for the NeuroShield.…”
Section: B Neural Networksupporting
confidence: 54%
“…Recently, some works have discussed the reliability of EdgeAI devices to neutrons and protons, focusing specifically the Arduino NeuroShield [1], [2]. To the best of our knowledge, this is the first work presenting experimental data on Coral TPU devices error rate.…”
Section: Cnns Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…As EdgeAI devices are likely to be used at scale and in distributed systems, it is fundamental to investigate their reliability, in particular their neutron-induced error rate. Preliminary studies showed that, despite being small, EdgeAI devices have a nonnegligible neutrons-or protons-induced error rate (BLOWER et al, 2021;BREWER et al, 2020).…”
Section: Palavrasmentioning
confidence: 99%